In vitro antimicrobial activity of leaves of Acalypha indica Linn. (Euphorbiaceae) - Abdullah, Muhammad Nazrul Hakim; Abdul Rashid, R.; Abdullah, Abdul Salam; Ahmad, Zuraini; Zakaria, Zainul Amiruddin; Sulaiman, Mohd Roslan; Abdul Kadir, Arifah; Abdul Mutalib, Abdul Rahim (Academic Journals, 2010)
The antimicrobial activity of water, ethanol and chloroform extracts of Acalypha indica was tested against four bacterial and fungal strains using the disc diffusion method. The antibacterial activity against gram positive bacteria was more pronounced (p < 0.05) in water and ethanol extracts. Antifungal activity was more significant (p < 0.05) only in chloroform extract. This antimicrobial activity was compared to standard antibiotics (penicillin, enrofloxacin, ampicillin and chlorampenicol) and antifungal drugs (ketoconazole, itraconazole and fluconazole). Findings from current study support the use of Acalypha indica in traditional medicine for the treatment of various bacterial and fungal infections.